Geomorphology of the lower Mesopotamian plain at Tell Zurghul archaeological site - Giulia Iacobucci; Francesco Troiani; Salvatore Milli; Davide Nadali (Journal of Maps, 2023)
ABSTRACTThe landscape of the Lower Mesopotamia Plain (LMP) has been moulded by water-related processes, consequently, its Holocene geomorphic evolution has been strictly connected to the fluvial process and the anthropogenic water management since 8000 BC. About 6000 years ago, during the maximum marine ingression, the modern cities of Nasiriyah and Al-Amara were close to the Persian Gulf shoreline. Successively, the Tigris and Euphrates developed two wide delta systems, that prograded south-eastward developing a complex fluvial network. Remote sensing investigations over the LMP using satellite imagery and topographic analysis revealed the surficial expression of deltaic bodies with a lobate planform and several terminal distributary channels (TDCs), classifiable as tidal-influenced river-dominated deltas. Tell Zurghul archaeological site, belonging to the ancient State of Lagash, expanded in the western part of the recognized TDC during the Mid- and Late Holocene. Indeed, the occurrence of a divergent multi-channel system supplied water for the early civilizations, which improved the water management and prevented floods through a canals network. Therefore, the multi-sensor remote sensing approach over an area of 2850 km2 allowed us to recognize several fluvial landforms, both still active and relict, attributable to the Holocene riverscape of the LMP, as well as anthropogenic features and aeolian deposits. The Main map is a geomorphological map at the scale of 1:120,000 centred on Tell Zurghul, focusing on the geometry, spatial distribution, and state of activity of erosional and constructional landforms.